Video reflection with a literacy coach: the mediation of teacher agency. Issue 5 (3rd September 2022) - Reichenberg, Jennifer Sharples
ABSTRACT: This multiple case study examines the use of a reflective process and lesson video by teachers of adolescent emergent multilingual students within the context of literacy coaching. Analysis of data from four teachers and a coach across seven months explored the relationship between video reflection using a seven-step reflective process and teacher agency in coaching. Video reflection has potential to emphasize teacher agency in coaching, particularly important in complex secondary settings in which teachers and coaches often possess differing expertise. Findings showed that actions taken by teachers while reflecting with video that led to teachers exercising agency were 1) noticing and considering students' perspectives and 2) inferring. These actions were associated with pedagogical changes to increase student engagement, improve instructional scaffolding, and integrate peer and first-language support. Discussion will highlight sociocultural theory to explain mediation by the reflective process and the video. This study shows the potential of video and a reflective process implemented as part of literacy coaching to impact teacher agency to take action supporting student learning in complex contexts. Suggestions for applying this reflective process in contexts without a coach and contexts in which it is not possible to video record are included.